Factors Influencing Use of Web for Academic Pursuit in Relation to User Categories - Datta, Swati; Kumar, Shiv (DESIDOC Journal of Library & Information Technology, 2023)
This paper examines the factors accountable for users’ tendency to use the free web resources for achieving their academic goals and also the reasons that prevented the users from using the credible sources of the library for their academic needs. Further, this study also attempted to ascertain whether user category has any influence on the factors which boost the use of web for academic purpose. A questionnaire- based survey was conducted for five universities of Chandigarh, Haryana and Punjab including post graduate students, research scholars and faculty members. The findings showed that a majority of respondents from three categories chose the web because of the speedy retrieval of information, ease of access, no need for any advanced search skills to search on internet and further it saved their time when compared with the online e-resources subscribed by the library. Most of them found it difficult to physically visit the library. They were not familiar with which e-resources were available on subscribed databases or on the web. About half of users stated that no updation was made on the library website about newly subscribed e-resources. Discontinued e-resources were not removed from library website when users searched them for information and found nothing. The paper recommends that user education programmes should be conducted and the interface of the library should be made user friendly so as to encourage the users to use authentic information from the e-resources subscribed by the library for academic purpose.